National testing in education in France: Statisation, rationalisation and politicisation. (March 2020) - Pons, Xavier
In this paper, we analyse the trajectory of the French testing policy in education since 1973. Regarding its statistical tradition and its ability to produce its own evaluation tool, France may be regarded as an interesting case to interrogate the capacity of national educational systems to meet international standards of testing. Anchored in a perspective of sociology of public action, we show that the development of testing in France is the outcome of specific policy configurations that themselves depend on various types of factors. Using materials drawn from four qualitative research studies on testing and evaluation, we argue that this policy trajectory can be interpreted as a statisation process in which state administrations and political leaders both increased their power on society and imposed their categories and own interests to policy actors. This statisation led to a rationalisation and a politicisation of testing. Testing development did not lead in France to a deep transformation of governance patterns: it rather merged into traditional modes of regulation of education and confirmed them to some extent. Testing is thus an interesting way to study the propensity of the French education system to redefine global problems according to domestic stakes.